2017
DOI: 10.1175/jpo-d-16-0178.1
|View full text |Cite
|
Sign up to set email alerts
|

Submesoscale Instabilities in Mesoscale Eddies

Abstract: Submesoscale processes have been extensively studied in observations and simulations of fronts. Recent idealized simulations show that submesoscale instabilities also occur in baroclinic mesoscale cyclones and anticyclones. The instabilities in the anticyclone grow faster and at coarser grid resolution than in the cyclone. The instabilities lead to larger restratification in the anticyclone than in the cyclone. The instabilities also lead to changes in the mean azimuthal jet around the anticyclone from 2-km re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 67 publications
(108 reference statements)
6
68
1
Order By: Relevance
“…Brannigan () and Brannigan et al () predict that symmetric instabilities will be strongest near the periphery of anticylonic eddies. We use sea level anomaly measurements from AVISO (Archiving, Validation and Interpretation of Satellite Oceanographic data), where positive (negative) values of sea level anomaly correspond to cyclones (anticylones; Figure c, black).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Brannigan () and Brannigan et al () predict that symmetric instabilities will be strongest near the periphery of anticylonic eddies. We use sea level anomaly measurements from AVISO (Archiving, Validation and Interpretation of Satellite Oceanographic data), where positive (negative) values of sea level anomaly correspond to cyclones (anticylones; Figure c, black).…”
Section: Resultsmentioning
confidence: 98%
“…Increasing (decreasing) will deepen (shoal) the mixed layer, and indeed short-lived deepenings of the mixed layer in May and June correspond to increases in (Figure 9a). Brannigan (2016) and Brannigan et al (2017) predict that symmetric instabilities will be strongest near the periphery of anticylonic eddies. We use sea level anomaly measurements from AVISO (Archiving, Validation and Interpretation of Satellite Oceanographic data), where positive (negative) values of sea level anomaly correspond to cyclones (anticylones; Figure 9c, black).…”
Section: External Forcing and Submesoscale-instability Exportmentioning
confidence: 99%
“…Moreover, the spatial resolution of the data (~4 km) is still not fine enough to resolve all the submesoscale structures. According to the simulation in Brannigan et al (), both the relative vorticity and the surface temperature in eddies show increasing numbers of small‐scale structures as the model resolution increases from 4 to 0.25 km. Thus, with higher‐resolution data, we would expect greater contributions from submesoscale structures to high CHL.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, these observations are consistent with a study that showed, based on measurements and modeling, small‐scale variations in strain, divergence, and vorticity in the eddy core (Zhong et al, ). A numerical study (Brannigan et al, ) showed similar vertical structure of a passive tracer in the eddy core with a decrease in grid size to 250 m. Both studies attributed the small‐scale vertical structures to mixed layer instability and ageostrophic dynamics.…”
Section: In Situ Observations and The Dual‐core Vertical Eddy Structurementioning
confidence: 94%
“…The mesoscale patterns of eddies has been extensively observed, but the nonlinear dynamics and the interactions with the atmosphere generating finer‐scale motions have mainly been explored only numerically and theoretically. Recent high‐resolution numerical modeling of eddies have described submesoscale processes (Brannigan, ; Brannigan et al, ; Zhong et al, ). Likewise, observed eddies appear often more complex than expected.…”
Section: Introductionmentioning
confidence: 99%